Отрицание как категория грамматики и способы его выражения (На материале русского и литовского языков) - Казимянец, Е. Г. (Kalbotyra, 1987)
The definition of this linguistic category is given basing on the analysis of the existing viewpoints concerning the nature of negation. The ways and means of expressing negation in the Russian and Lithuanian languages are considered, and their classification is proposed. It is shown that identical linguistic means are used for expressing negation in both languages, a complete correspondence in the usage of these units is not observed.